E.COLİ (MK79) REKOMBİNANT SUŞU İLE ?-AMİLAZ ÜRETİM ORTAMININ İNCELENMESİ - TANAYDIN, ZÜMRA BAKICI (Fırat Üniveristesi, 2012)
[Abstract Not Available]
E. coli (MK79) with recombinant strain investigation of ?-amylase pproduction environment
Keywords: Kimya Mühendisliği